Pemenuhan Vaksinasi Covid-19 Sebagai Hak Atas Kesehatan Bagi Masyarakat Adat di Indonesia: Fulfillment of Covid-19 Vaccination as the Right to Health for Indigenous Peoples in Indonesia - Pratama, Anugrah Muhtarom (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
This article aims to answer how the government's efforts in realizing the fulfillment of Covid-19 vaccination as a right to health for indigenous peoples during the pandemic. Giving Covid-19 vaccination to every citizen has now become an effort in resolving the Covid-19 pandemic. One of the vulnerable groups in the Covid-19 pandemic is indigenous people who have previously been vulnerable due to limited access to health. This article is normative legal research using a statutory approach. The result is that the government has included indigenous peoples into vaccination priorities in Regulation of the Minister of Health No. 84 of 2020. Furthermore, the government's vaccination priority provisions have also been in accordance with the principle of non-discrimination in who's the provision that indigenous peoples are included in vaccination priorities as sociodemographic groups. In this regard, the government has implemented Article 28H paragraph (1) of the 1945 Constitution which stipulates that every citizen is entitled to health services. Furthermore, in the implementation in the field, covid-19 vaccination is only done for Indigenous peoples in Bali. This is done because Bali relies heavily on the tourism sector which is also a lot of custom-based tourism. Meanwhile, baduy indigenous people are vaccinated because their territory is included in the red zone of the spread of Covid-19.